EVALUASI PARADE “OGOH-OGOH” SEBAGAI PENDUKUNG PENGEMBANGAN PARIWISATA BUDAYA DI KOTA DENPASAR - Aristrawati, Ni Luh Putu (JURNAL MASTER PARIWISATA, 2015)
This article discusses the evaluation of giant effigy ogoh-ogohparade based on three aspects, such as the implementationof ogoh-ogoh parade, the contribution of ogoh-ogoh paradeto the development of cultural tourism in Denpasar and toprovide recommendations for strategy implementation of ogohogohparade. This article was used culture tourism theory andevaluation theory. The data presented in this article was collectedthrough observation and is complemented by interviews andother published sources with qualitative approach. The collecteddata analyzed by CIPP (Context, Input, Process and Product)evaluation model, expert judgment and qualitative descriptive.The result shows that parade ogoh-ogoh meet the criteria as anevent that contributes in an effort to realize Denpasar as culturalcity. Ogoh-ogoh parade also contributes as a supporting Denpasarin developing cultural tourism. The implementation strategyof ogoh-ogoh parade can be done through by the competitionstrategy and the increasing promotion strategy. From this articleit can be concluded that as one of the cultural event in Denpasarcity ogoh-ogoh parade can support the development of culturaltourism in the city of Denpasar, although in its implementation itrequires sustain improvement.
Keywords: Evaluation, Ogoh-ogoh Parade, Cultural Tourism, Promotion Strategy